2023
DOI: 10.1186/s13046-023-02769-z
|View full text |Cite
|
Sign up to set email alerts
|

A GATA2-CDC6 axis modulates androgen receptor blockade-induced senescence in prostate cancer

Abstract: Background Prostate cancer is a major cause of cancer morbidity and mortality in men worldwide. Androgen deprivation therapy (ADT) has proven effective in early-stage androgen-sensitive disease, but prostate cancer gradually develops into an androgen-resistant metastatic state in the vast majority of patients. According to our oncogene-induced model for cancer development, senescence is a major tumor progression barrier. However, whether senescence is implicated in the progression of early-stag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 77 publications
0
0
0
Order By: Relevance
“…Furthermore, EMT (de-differentiation) of PC cells has also been shown to be induced by AR splice variants, like AR-V7, that can be constitutively active in the nuclei independently of androgen regulation [78,79]. Mourkioti et al recently demonstrated a significant interplay between the GATA2-CDC6 signaling axis and PC senescence; the treatment of androgen-sensitive cells with enzalutamide led to down-regulation of CDC6 through the GATA2 transcription factor and, eventually, to senescence, while enzalutamide-resistant PC cells displayed stable CDC6 levels, EMT activation and a higher invasive potential [80].…”
Section: Prostate Cscs (Pcscs) Characterizationmentioning
confidence: 99%
“…Furthermore, EMT (de-differentiation) of PC cells has also been shown to be induced by AR splice variants, like AR-V7, that can be constitutively active in the nuclei independently of androgen regulation [78,79]. Mourkioti et al recently demonstrated a significant interplay between the GATA2-CDC6 signaling axis and PC senescence; the treatment of androgen-sensitive cells with enzalutamide led to down-regulation of CDC6 through the GATA2 transcription factor and, eventually, to senescence, while enzalutamide-resistant PC cells displayed stable CDC6 levels, EMT activation and a higher invasive potential [80].…”
Section: Prostate Cscs (Pcscs) Characterizationmentioning
confidence: 99%